Molecularly Imprinted Nanofiber Membranes: Localization of Molecular Recognition Sites on the Surface of Nanofiber - Isezaki, Jun; Yoshikawa, Masakazu (Journal of Membrane and Separation Technology, 2014)
Two types of molecularly imprinted nanofiber membrane were fabricated from chitosan, adopting D-phenylalanine (D-Phe) or L-phenylalanine (L-Phe) as a print molecule. Molecularly imprinted nanofiber membranes were fabricated by applying a co-axial, two capillary spinneret so that molecular recognition sites could be localized on the surface of formed nanofiber. Though the effect was not so prominent, the amount of molecular recognition site for nanofibers with localized molecular recognition site (core-shell molecularly imprinted nanofiber membranes) was higher than that with delocalized one (usual molecularly imprinted nanofiber membranes). Those membranes showed permselectivity. The enantiomer preferentially incorporated into membrane was selectively transported.